Channels of distribution - Doherty, Anne Marie (Henry Stewart Talks, 2014)
Channels of distribution/marketing channels, Types of distribution channel: consumer, B2B, service, Channel intermediaries, Retailers: ownership and format, Distribution intensity, Channel strategy, Vertical marketing systems, Logistics and supply chain management, Grocery and fashion supply chains, Channel relationships, Franchising as a marketing channel, Franchise market and partner selection, Franchise relationships, Support, power and control in the franchise channel